Recent advances and perspectives in the synthesis of bioactive coumarins. Issue 52 (11th May 2016) - Calcio Gaudino, E.; Tagliapietra, S.; Martina, K.; Palmisano, G.; Cravotto, G.
Abstract : The impressive pharmacological properties shown by a number of coumarins have led to extraordinarily large emphasis being placed on the design of more efficient and greener synthetic procedures to produce them. Abstract : The impressive pharmacological properties shown by a number of coumarins have led to extraordinarily large emphasis being placed on the design of more efficient and greener synthetic procedures to produce them. The increasing use of enabling technologies, such as microwaves, ultrasound, new heterogeneous catalysts and greener solvents in recent years has made access to coumarin derivatives much simpler. This review will highlight the most recent synthetic advances that make use of non-conventional methods and energy sources and some perspectives for the future, in particular the synthesis of new hybrid molecules bearing a coumarin moiety with a dual mode of biological action.